Kinetics of Photosynthetic Response to Ultraviolet and Photosynthetically Active Radiation in Synechococcus WH8102 (CYANOBACTERIA). (28th November 2013) - Fragoso, Glaucia M.; Neale, Patrick J.; Kana, Todd M.; Pritchard, Alicia L.
Abstract The picoplanktonic cyanobacteria, Synechococcus spp., (Nägeli) are important contributors to global ocean primary production that can be stressed by solar radiation, both in the photosynthetically active (PAR) and ultraviolet (UV) range. We studied the responses of PSII quantum yield (active fluorescence), carbon fixation (14C assimilation) and oxygen evolution (membrane inlet mass spectrometry) in Synechococcus WH8102 under moderate UV and PAR. PSII quantum yield decreased during exposure to moderate UV and UV+PAR, with response to the latter being faster (6.4 versus 2.8 min, respectively). Repair processes were also faster when UV+PAR exposure was followed by moderate PAR (1.68 min response time) than when UV was followed by very low PAR (10.5 min response time). For the UV+PAR treatment, the initial decrease in quantum yield was followed by a 50% increase ("rebound") after 7 min exposure, showing an apparent photoprotection induction. While oxygen uptake increased with PAR, it did not change under UV, suggesting that this oxygen‐dependent mechanism of photoprotection, which may be acting as an electron sink, is not an important strategy against UV. We used propyl gallate, an antioxidant, to test for plastid terminal oxidase (ptox) or ptox‐like enzymes activity, but it caused nonspecific and toxic effects on Synechococcus WH8102.